How should we measure maternal mortality in the developing world? A comparison of household deaths and sibling history approaches - Hill Kenneth; El Arifeen Shams; Koenig Michael; Al-Sabir Ahmed; Jamil Kanta; Raggers Han (The World Health Organization, 2006)
OBJECTIVE: A reduction in the maternal mortality ratio (MMR) is one of six health-related Millennium Development Goals (MDGs). However, there is no consensus about how to measure MMR in the many countries that do not have complete registration of deaths and accurate ascertainment of cause of death. In this study, we compared estimates of pregnancy-related deaths and maternal mortality in a developing country from three different household survey measurement approaches: a module collecting information on deaths of respondents' sisters; collection of information about recent household deaths with a time-of-death definition of maternal deaths; and a verbal autopsy instrument to identify maternal deaths. METHODS: We used data from a very large nationally-representative household sample survey conducted in Bangladesh in 2001. A total of 104 323 households were selected for participation, and 99 202 households (95.1% of selected households, 98.8% of contacted households) were successfully interviewed. FINDINGS: The sisterhood and household death approaches gave very similar estimates of all-cause and pregnancy-related mortality; verbal autopsy gave an estimate of maternal deaths that was about 15% lower than the pregnancy-related deaths. Even with a very large sample size, however, confidence intervals around mortality estimates were similar for all approaches and exceeded ?15%. CONCLUSION: Our findings suggest that with improved training for survey data collectors, both the sisterhood and household deaths methods are viable approaches for measuring pregnancy-related mortality. However, wide confidence intervals around the estimates indicate that routine sample surveys cannot provide the information needed to monitor progress towards the MDG target. Other approaches, such as inclusion of questions about household deaths in population censuses, should be considered.